Apelin Inhibits Diet-Induced Obesity by Enhancing Lymphatic and Blood Vessel Integrity - Sawane, Mika (American Diabetes Association, 2013)
Angiogenesis is tightly associated with the outgrowth of adipose tissue, leading to obesity, which is a risk factor for type 2 diabetes and hypertension, mainly because expanding adipose tissue requires an increased nutrient supply from blood vessels. Therefore, induction of vessel abnormality by adipokines has been well-studied, whereas how altered vascular function promotes obesity is relatively unexplored. Also, surviving Prox1 heterozygous mice have shown abnormal lymphatic patterning and adult-onset obesity, indicating that accumulation of adipocytes could be closely linked with lymphatic function. Here, we propose a new antiobesity strategy based on enhancement of lymphatic and blood vessel integrity with apelin. Apelin knockout (KO) mice fed a high-fat diet (HFD) showed an obese phenotype associated with abnormal lymphatic and blood vessel enlargement. Fatty acids present in the HFD induced hyperpermeability of endothelial cells, causing adipocyte differentiation, whereas apelin promoted vascular stabilization. Moreover, treatment of apelin KO mice with a selective cyclooxygenase-2 inhibitor, celecoxib, that were fed an HFD improved vascular function and also attenuated obesity. Finally, apelin transgenic mice showed decreased subcutaneous adipose tissue attributable to inhibition of HFD-induced hyperpermeability of vessels. These results indicate that apelin inhibits HFD-induced obesity by enhancing vessel integrity. Apelin could serve as a therapeutic target for treating obesity and related diseases.